Production and characterization of cr and crn hard coatings deposited by unbalanced magnetron sputtering (2013)
In this work, we present the results of Cr and CrN coatings deposited using unbalanced magnetron sputtering at different substrate temperatures. The layers with thickness and lt; 1μm were produced at different temperatures (100, 300 and 500 oC) on AISI H13 steel and (100) Silicon and analyzed by XRD and SEM techniques. In both cases the diffraction peaks showed slight shifts as a function of substrate temperature. These shifts could be an indicative of the presence of compressive stress, which increases with temperature. Additionally, the analyses of scanning electron microscope (SEM) showed that the coated surfaces at temperatures and lt; 500 oC, are characterized mainly by a morphology with a smooth appearance, compact, homogeneous and displayed columnar growth, without evidence neither of microcracking nor delamination. This behavior suggests that in this temperature range, there is a slight dependence on the substrate temperature. On the contrary, samples prepared at 500 oC showed the presence of larger grains and a more compact growth.